Corrosion Resistance, Friction and Wear Properties of Cemented Carbide Coatings under Variable Temperature - ZHANG Shuai, MA Yu - shan, DAI Wan - xiang, HE Tao, CHANG Zhan - dong, LIU Hai - bo, JIA Hua, JI Hua (Cailiao Baohu)
Cemented carbide coatings such as WC - 10Co4Cr and NiCr - Cr3C2 have strong corrosion resistance and wear resistance, and so they are often used in various corrosive and wearing environments. In order to study the effect of temperature changes on the corrosion and friction properties of cemented carbide coatings, the high velocity oxygen fuel spraying process was used to prepare WC - 10Co4Cr and NiCr - Cr3C2 coating on 304 stainless steel substrates. The corrosion resistance changed with the temperature variation and the effect of corrosion on the wearing properties were studied by XRD, electrochemical test and sliding wear test. Result showed that when temperature changed from 25 ℃ to 60 ℃, the corrosion current density in 0.5 mol/L H2SO4 solution increased 2.7 times for WC - 10Co4Cr coating and 23.9 times for NiCr - Cr3C2 coatings, respectively. In the sliding test, the mass loss of WC - 10Co4Cr coating with the sapphire grinding ball is 1 mg before corrosion, which was is about 20% of the mass loss for NiCr - Cr3C2 coatings. In contrast, the mass loss increased 1.9 times for WC - 10Co4Cr and 2.9 times for NiCr - Cr3C2 sample after corrosion. Besides, the main failure mode of WC - 10Co4Cr coating was abrasive wear, while that of NiCr - Cr3C2 coating contained the abrasive wear and adhesive wear during sliding wear test. Moreover, corrosion could increase the wear rate of the coating and affect the friction behavior of the coating during the running - in stage.